Functional Significance of Sialidase During Influenza Virus Multiplication: an Electron Microscope Study - Seto, J. T. (1969)
Morphological evidence has been obtained by electron microscopy in support of previous findings that one of the most important functions of sialidase is associated with the release of virus from infected host cells. Highly specific antiserum against fowl plague virus enzyme and specific antiserum against X7 recombinant influenza virus enzyme were shown to influence the morphology of cells infected with their homologous virus. In the presence of enzyme antiserum, an accumulation and aggregation of virus particles were evident on the cell surface and in the extracellular space of infected host cells. The aggregation of virus particles was interpreted to result from the inhibition of the release of virus.